Why do business processes deviate? Results from a Delphi study - Ko ¨ nig, Ulrich Matthias (Springer Nature, 2020)
Abstract Despite substantial investments in business process management (BPM),every organization experiences deviant processes, i.e., processes that show different behavior than intended. Thus, process deviance is an essential topic of BPM research and practice. Today, research on process deviance is mainly driven from a computer science perspective. IT-based methods and tools (e.g., deviance mining and prediction or compliance checking) detect process deviance by comparing log data from past process instances with formative process models or execution traces of currently running instances. However, requiring process models and event logs as input, existing approaches are expensive and limited to processes executed in automated workﬂow environments. Further, they can only detect process deviance, not explain why it occurs. Thus, knowledge about reasons for process deviance is immature. What is missing is a systematic exploration of reasons for process